Estimating the Health Care Demand for Iran - Mina BaniAsad; HamidReza Horry (Shahid Sadoughi University of Medical Sciences, 2017)
Background: When trying to estimate demand elasticity, it is important to first obtain an appropriate estimation of the demand function. One of the best methods for estimating the demand for healthcare services that is part of the household cost is the use of the almost ideal demand system (AIDS). The purpose of this study was to making better decisions when estimating the demand elasticity for healthcare services. Methods: This research is a descriptive-analytic study. The statistical population of this study is the Iranian population for the years 1990 to 2011. The required data were collected from the Central Bank of the Islamic Republic of Iran. In this research, the demand for healthcare services was estimated using the AIDS model by the method of estimating seemingly unrelated regressions (SUR). Results: According to the estimates, the income elasticity for the demand of healthcare services in the household budget is slightly larger than one and the self-priced elasticity is close to one and the cross elasticity between the change in house prices and the share of healthcare services is a negative value and close to zero and the cross elasticity between food prices and the share of healthcare services is positive and near zero and the cross elasticity between clothing prices and the share of health care services in the household budget is zero. Conclusion: Since the income elasticity of demand for healthcare services is greater than one, it is necessary for the government to increase the share of health care budget so that low-income groups can use these services. Furthermore, the price elasticity of healthcare services is one; therefore, a steady rise in the price of health care services cannot lead to a sharp decline in using these services for households.